2022
DOI: 10.1002/ana.26296
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Brain LPC‐DHA by Plasma Supplementation Attenuates Brain Injury after Cardiac Arrest

Abstract: Objective Cardiac arrest (CA) is a major health burden with brain damage being a significant contributor to mortality. We found lysophosphatidylcholine (LPC), including a species containing docosahexaenoic acid (LPC‐DHA), was significantly decreased in plasma post‐CA, supplementation of which significantly improved neurological outcomes. The aim of this study is to understand the protective role of LPC‐DHA supplementation on the brain post‐CA. Methods We first evaluated associations between the plasma level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Additionally, defects in nuclear genes can lead to phospholipid metabolism disorders, particularly in mitochondrial diseases like Barth syndrome and dilated cardiomyopathy [14,15]. Recent investigations, including our own study, suggest that alterations in phospholipids, particularly within mitochondria, may significantly contribute to brain dysfunction following cardiac arrest [16][17][18][19]. This review aims to explore the potential involvement of mitochondrial phospholipids in neural damage subsequent to cardiac arrest, with the objective of enhancing our comprehension of the pathophysiological mechanisms driving post-cardiac arrest brain injury.…”
Section: Introduction To Phospholipidsmentioning
confidence: 84%
“…Additionally, defects in nuclear genes can lead to phospholipid metabolism disorders, particularly in mitochondrial diseases like Barth syndrome and dilated cardiomyopathy [14,15]. Recent investigations, including our own study, suggest that alterations in phospholipids, particularly within mitochondria, may significantly contribute to brain dysfunction following cardiac arrest [16][17][18][19]. This review aims to explore the potential involvement of mitochondrial phospholipids in neural damage subsequent to cardiac arrest, with the objective of enhancing our comprehension of the pathophysiological mechanisms driving post-cardiac arrest brain injury.…”
Section: Introduction To Phospholipidsmentioning
confidence: 84%
“…Lysophosphatidylcholine containing docosahexaenoic acid (LPC-DHA) is a form of omega-3 fatty acid, which is significantly decreased in post-CA plasma in rats and humans [ 63 ]. In a 10-minute asphyxia rat CA model, IV injection of 6 mg/kg LPC-DHA (0.5 mL) 1 minute after ROSC over 1 minute significantly improved neurological functions as assessed by neuronal reflex test and motor coordination test at 72 hours after ROSC [ 64 ]. Supplementation of LPC-DHA normalized brain levels of LPC-DHA and alleviated neuronal cell death, activation of astrocytes, and expression of various inflammatory and mitochondrial dynamics genes.…”
Section: Neuroprotective Approaches In Ca-induced Brain Injurymentioning
confidence: 99%
“…It is proposed that low availability of LPC-DHA may play a causative role for brain injury after cardiac arrest [58 ▪ ]. In rats, supplementing with LPC-DHA normalized brain levels of LPC-DHA and alleviated neuronal cell death, activation of astrocytes, and expression of various inflammatory and mitochondrial dynamics genes [59]. Another study observed that acute brain injury (intracerebral hemorrhage) triggers the synthesis of neuroprotectin D1, a DHA-derived SPM: neuroprotectin D1 levels were higher in patients with better 90-day outcome [60].…”
Section: Omega-3 Polyunsaturated Fatty Acids Brain Injury and Neurolo...mentioning
confidence: 99%